2017
DOI: 10.20944/preprints201708.0088.v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a Data Set of Pesticide Dissipation Rates in/on Various Plant Matrices for the Pesticide Properties Database (PPDB)

Abstract: Data relating to the rate at which pesticide active substances dissipate on or within various plant matrices are important for a range of different risk assessments; however, despite the importance of this data, dissipation rates are not included in the most common online data resources. Databases have been collated in the past, but these tend not to be maintained or regularly updated. The purpose of the exercise described herein was to collate a new database in a format compatible with the main online pestici… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…When no data were available, the inputs were calibrated. 21,24,28,29) The curve number value used in the simulation was extracted from the tables provided by the SCS Engineering Division and is appropriate for a 5% slope with bare soil (no crop residue) and a soil with moderate infiltration rate. 19) Previous analysis indicated that the curve number method was applicable for the andisol soil plot scale with bare soil.…”
Section: Model Parameterizationmentioning
confidence: 99%
“…When no data were available, the inputs were calibrated. 21,24,28,29) The curve number value used in the simulation was extracted from the tables provided by the SCS Engineering Division and is appropriate for a 5% slope with bare soil (no crop residue) and a soil with moderate infiltration rate. 19) Previous analysis indicated that the curve number method was applicable for the andisol soil plot scale with bare soil.…”
Section: Model Parameterizationmentioning
confidence: 99%